The Role and Views of Ophthalmologists During the COVID-19 Pandemic - Kortuem FC (Dove Medical Press, 2021)
Friederike C Kortuem,1,* Focke Ziemssen,1,2,* Karsten U Kortuem,3 Constanze Kortuem1 1University Eye Hospital, Center for Ophthalmology, University of Tübingen, Tübingen, Germany; 2Department of Ophthalmology, University Hospital Leipzig, Leipzig, Germany; 3University Eye Hospital Ulm, University of Ulm, Ulm, Germany*These authors contributed equally to this workCorrespondence: Focke ZiemssenDepartment of Ophthalmology, University Hospital Leipzig, Liebigstr. 12, Leipzig, 04103, GermanyTel +49 341 97 21650Fax +49 341 97 21659Email focke.ziemssen@med.uni-tuebingen.dePurpose: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic forced ophthalmologists to adjust their working conditions to ensure patient and staff safety, while still providing effective and timely treatment. This international survey among ophthalmologists was initiated to capture what actions ophthalmologists were taking and what their opinions were on the risks of infection in their workplace, the delay in treatment, the use of telemedicine and telephone for appointments, and the regional specifications and measures implemented by the respective authorities.Methods: An open-source web tool was used to develop an online survey, to which ophthalmologists worldwide were invited via e-mail using international mailing lists (Media Mice, Singapore; Texere Publishing Inc, USA; CGO Gerling) and incentivized using a lottery. The physicians provided their level of agreement relating to the offered statements and gave free answers to the questions regarding the actions taken (conducted November 5th 2020 to December 20th 2020).Results: After 91,000 invitations, responses were collected from 1122 ophthalmologists. Despite the use of large international mailing lists, mainly doctors from Europe participated. Half of the participants expressed great concern about possible SARS-CoV-2 infection in their patients. A significant number of younger ophthalmologists (≤ 50 years: 76.9%, n = 313; > 50 years: 69.6%, n = 181) feared the delays that COVID-19 could cause to treatment. Reductions in patient numbers were broadly observed, with more ophthalmologists of younger age reporting greater declines. Nearly all ophthalmologists indicated that they provided disinfectant and the majority also used masks and questionnaires for screening. For 60.3% (n = 412) of ophthalmologists, telephone calls reduced the risk of ‘no-shows’; 71.6% (n = 497) disagreed that telemedical evaluation is possible without slit lamp findings and fundus photos; and 57.0% of participants felt content with the governmental measures during the COVID-19 pandemic.Conclusion: The COVID-19 pandemic has significantly influenced the work of ophthalmologists. Based on the limited response rate, certain statements were only possible to evaluate for the European Union: with a noticeable reduction in patient numbers, delay in treatment was a major worry. Measures to protect and reassure patients should be undertaken, especially regarding those with vision-threatening diseases requiring treatment.Keywords: COVID-19, survey, infection control, occupational safety